Formation of a Safe Digital Educational Environment as the Basis for Solving Economic Security Problems in the Conditions of the Formation of an Innovative Economy - Chvyakin Vladimir Alekseevich; Zhakhov Nikolay Vladimirovich; Tarakanov Alexander Valerievich; Orlov Vitaly Vladimirovich (Communications of International Proceedings, 2020)
The central link in ensuring economic security in the education system is the economic security of an educational organization. The economic security of an educational organization depends on a large number of factors of a very different nature, duration and scale, which determines its essence. Three groups of factors of economic security of an educational organization have been identified. As indicators of the degree of risk, it is advisable to use risk coefficients showing the likelihood of unfavorable outcomes when the goal of a certain level is achieved by one of the interested parties. Special types of risks for education are presented. The work highlights two aspects of information security: protection from the negative impact of the influencing information environment and the provision of a basis for positive socialization and individualization of the teacher in the context of achieving a high level of education quality.
Keywords: Digital Educational Environment; Economic Security; Information Security; Innovative Economy.